Dari Sekularisasi Menuju Reintegrasi Pengetahuan: Analisis Filsafat Ilmu dalam Pembaruan Sains Global - Sidqi Ali; Shinta Adhelia Putri Sugiharto; Munirul Abidin (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The progress of modern science, grounded in rational and empirical approaches, has significantly contributed to human advancement while also producing epistemological challenges, particularly the secularization of knowledge that separates science from values and transcendent meaning. This condition has stimulated criticism of the claim of value neutrality in science and exposed the limitations of secular paradigms in addressing ethical, social, and human concerns. This study aims to analyze the transition from the secularization toward the reintegration of knowledge from the perspective of the philosophy of science and its relevance to the renewal of global science. Employing a qualitative literature review, this research critically examines scholarly works in the philosophy of science, sociology of knowledge, and integrative science studies published over the past decade. The findings demonstrate that although secularization remains influential in modern scientific epistemology, there is increasing scholarly recognition of the importance of integrating values into scientific practice. The reintegration of knowledge is proposed as a holistic paradigm that unites empirical, rational, ethical, and transcendent dimensions. The philosophy of science thus serves as a reflective and normative foundation for guiding scientific development toward ethical responsibility, social well-being, and meaningful human existence within a global context.